Peptides presenting the binding site of human CD4 for the HIV-1 envelope glycoprotein gp120 - Meier, Julia; Kassler, Kristin; Sticht, Heinrich; Eichler, Jutta (Beilstein Journal of Organic Chemistry, 2012)
Based on the structure of the HIV-1 glycoprotein gp120 in complex with its cellular receptor CD4, we have designed and synthesized peptides that mimic the binding site of CD4 for gp120. The ability of these peptides to bind to gp120 can be strongly enhanced by increasing their conformational stability through cyclization, as evidenced by binding assays, as well as through molecular-dynamics simulations of peptide–gp120 complexes. The specificity of the peptide–gp120 interaction was demonstrated by using peptide variants, in which key residues for the interaction with gp120 were replaced by alanine or D-amino acids.
Keywords: biomimetic synthesis; CD4; HIV entry; peptide; protein binding site